2012
DOI: 10.1111/j.1365-2265.2011.04242.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four‐hour profiles of plasma glucose, insulin, C‐peptide and free fatty acid in subjects with varying degrees of glucose tolerance following short‐term, medium‐dose prednisone (20 mg/day) treatment: evidence for differing effects on insulin secretion and action

Abstract: Objective To determine the time course and prandial effects of short-term, medium-dose prednisone on 24-hour metabolic patterns under standardized conditions. Context Glucocorticoids (GCs) adversely affect glucose homoeostasis but 24-hour profiles of glucose, insulin, C-peptide and free fatty acids (FFAs) following short-term, medium-dose prednisone treatment in persons with varying degrees of glucose tolerance are not well defined. Design An open-label cross-sectional interventional study. Subjects Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 36 publications
3
33
0
4
Order By: Relevance
“…Recent studies have indicated that GCs additionally impair a and b-cell function (5, 6, 7). In particular, postprandial metabolism is disturbed by GC treatment, resulting in characteristic hyperglycemia during the day and evening (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that GCs additionally impair a and b-cell function (5, 6, 7). In particular, postprandial metabolism is disturbed by GC treatment, resulting in characteristic hyperglycemia during the day and evening (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Only an increased gc dose and the interval in hours since the most recent gc dose or meal correlated with hyperglycemia for the bmt and cmt groups. Those positive correlations were expected, because increased doses of gc were previously shown to increase risk of hyperglycemia 18 , a longer interval since the administration of gc reflects the longer biologic half-life of synthetic gc (ranging from 8 hours to 72 hours 24 ), and a shorter interval since the most recent meal likely reflects the postprandial rise in serum glucose 40 . Although we collected data on the duration of gc exposure for the cmt and bmt groups, the duration of gc therapy was not significantly different in our patient groups, and we therefore cannot draw conclusions about a specific duration of gc therapy that leads to a greater hyperglycemia risk.…”
Section: Discussionmentioning
confidence: 98%
“…In the beginning of the 24-h feeding cycle, rats were fed for the first 2 h, then fasted for the remaining 22 h. For the simulation, glucose profiles corresponding to 2 h of food intake and 22 h of fasting based on 24-h profiles of plasma glucose (cf. Stanhope et al 2008;Yuen et al 2012) were used as periportal input profiles for the model (Fig. 8).…”
Section: Setup and Materials Parametersmentioning
confidence: 99%